Volatile Compound Detection of Banana Anthracnose Caused by Colletotrichum musae using Electronic Nose - Maksum, Muhammad; Putra, Yogi Kurnia; Chairuddin, Chairuddin; Gunawan, Hendra (Jurnal Agrikultura, 2025)
Food rotting is one of the many research topics that electronic nose technology can be used to target. This study examined the electronic nose capacity to detect the presence of Colletotrichum musae, the causative agent of anthracnose fruit rots on bananas using gas sensors by detecting the concentration of volatile compound. C. musae was identified visually and microscopically. Detached-fruit assay method was used in this experiment. A conidial fungal suspension at a concentration of 2.5 × 106 conidia/ml was injected into nine replication of homogenous banana samples, while nine other samples were injected with sterile aquadest served as negative controls. The information obtained from the electronic nose was analyzed using principal component analysis (PCA). The results showed that from six gas sensors used in the electronic nose, MQ-4, MQ-5, and MQ-8 were the gas sensors that have detected significant difference between the infected banana and the control with a concentration value of 166.83, 173.02, and 87.40 ppm in banana infected with C. musae and 20.90, 0.01, and 44.97 ppm in controls. Therefore, this three sensor can be used as a reference for detecting anthracnose disease in bananas.